Association between reactogenicity and SARS-CoV-2 antibodies after the second dose of the BNT162b2 COVID-19 vaccine. Issue 13 (18th March 2022) - Yamamoto, Shohei; Fukunaga, Ami; Tanaka, Akihito; Takeuchi, Junko S.; Inoue, Yosuke; Kimura, Moto; Maeda, Kenji; Ueda, Gohzoh; Mizoue, Tetsuya; Ujiie, Mugen; Sugiura, Wataru; Ohmagari, Norio
Abstract: High vaccine reactogenicities may reflect stronger immune responses, but the epidemiological evidence for coronavirus disease 2019 (COVID-19) vaccines is sparse and inconsistent. We observed that a fever of ≥38℃ after two doses of the BNT162b2 vaccine was associated with higher severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike IgG titers.